Antimicrobial Polymer-Based Hydrogels for the Intravaginal Therapies-Engineering Considerations - Monika Gosecka; Mateusz Gosecki (MDPI AG, 2021)
The review is focused on the hydrogel systems dedicated to the intravaginal delivery of antibacterial, antifungal and anti-Trichomonas vaginalis activity drugs for the treatment of gynaecological infections. The strategies for the enhancement of the hydrophobic drug solubility in the hydrogel matrix based on the formation of bigel systems and the introduction of nano- and microparticles as a drug reservoir are presented. Hydrogel carriers of natural and synthetic pharmacological substances, drug-free systems displaying antimicrobial activity thanks to the hydrogel building elements and systems combining the antimicrobial activity of both drug and polymer building components are distinguished. The design of hydrogels facilitating their administration and proper distribution in the vaginal mucosa and the vagina based on thermoresponsive systems capable of gelling at vaginal conditions and already-cross-linked injectable systems after reaching the yield stress are discussed. In addition, the mechanisms of hydrogel bioadhesion that regulate the retention time in the vagina are indicated. Finally, the prospects for the further development of hydrogel-based drug carriers in gynaecological therapies are highlighted.